The Development of Competitive Advantage Global Model of PT Tiphone Mobile Indonesia, Tbk: Case Study Using 4C Framework - Aryo Wicaksono; Rivaldi Arissaputra; Popy Rufaidah (Journal of International Conference Proceedings (JICP), 2018)
This paper discusses about the application of global competitive advantage with the 4C's Framework model (Hao Ma, 2004) that consists of Creation, Competition, Cooperation and Co-option variables.The research method used is case study that aims to present information in a structured, factual, and accurate way about the object that is under study. This study also uses SWOT Analysis method to identify strategic strengths and weaknesses as well as threats and opportunities facing the company. The results of the analysis are outlined in IFAS and EFAS analysis.The result of the research shows that the source of global competitive advantage of PT Tiphone Mobile Indonesia, Tbk. First, the Creation and Innovation variables are new product / market, effective organizational structure, organizational learning, superior corporate culture and creative human resource practice. Second, the Competition variables are timing and positioning, direct attack, flanking attack, and concentration. Third, the Cooperation variables are setting foothold, pooling resources, learning from partners, building alliances, weighing options. Fourth, the Co-option variables are enticiting the third party and co-opting customer. The application of these four variables produces a global competitive advantage variable that is divided into three types, namely ownership based, access based, and proficiency based.The research provides a managerial impact to the company that is under study, namely the implementation of 4C’s Framework model so the company has the advantage of competing globally. The Company achieves global competitive advantage based on ownership-based, access-based, and proficiency-based through the implementation of Creation and Innovation, Competition, Cooperation, and Co-option. Keywords: 4c’s framework, EFAS, IFAS, global competitive advantage, SWOT analysis.